Respiratory toxicity of carbon nanotubes: How worried should we be? - Muller, Julie; Huaux, François; Lison, Dominique (Carbon (New York), 2006)
The synthesis of carbon nanotubes (CNTs) and their actual and potential industrial uses have attracted the attention of many scientists world wide but relatively little attention has been paid, so far, to their potential detrimental effects on human health and the environment. Here, we briefly sketch the main determinants of the lung toxicity of inhaled particles and outline the existing experimental methods to explore their toxic potential to the lung. We then summarize the first available studies that have examined the respiratory toxicity of CNTs in experimental animals. Although data are still fragmentary and subject to criticisms, e.g. because of the non-physiological mode of administration used, the results indicate that if CNTs reach the lungs they can exert serious toxicity, manifested in experimental animals as inflammatory and fibrotic reactions. These reports represent a cause of concern for human health and indicate that strict preventive and protective measures should be taken to limit inhalation exposure to CNTs in occupational settings.